Analisis Kesulitan Belajar Siswa Pada Pembelajaran Matematika di Kelas IV SDN 01 Nanga Pinoh - Lestari, Sovia; Peterianus, Septian; Septiadi, Wahyu (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2025)
Abstract: This research aims to find out how students have difficulty learning in mathematics learning. The research method used is qualitative research. The results of research conducted at Nanga Pinoh 01 State Elementary School are that students' difficulties in learning mathematics include: 1) difficulties understanding concepts, 2) difficulties for students not memorizing multiplication, 3) difficulties in calculating, external factors for learning difficulties consist of parents and family lack of parental attention to children's learning habits at home. However, the difficulties in learning mathematics found in this research were that there were a small number who still experienced difficulties learning mathematics. Keywords: Learning Difficulties, Students, Mathematics Learning. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana kesulitan siswa belajar pada pembelajaran matematika. Metode penelitian yang digunakan adalah penelitian kualitatif. Hasil penelitian yang dilakukan di Sekolah Dasar Negeri 01 Nanga Pinoh adalah Kesulitan siswa belajar matematika meliputi: 1) kesulitan memahami konsep, 2) kesulitan siswa kurang hafal perkalian, 3) kesulitan dalam berhitung, faktor eksternal kesulitan belajar terdiri dari orang tua dan keluarga kurangnya perhatian orang tua terhadap kebiasaan belajar anak di rumah. Namun kesulitan belajar matematika yang ditemukan dalam penelitian ini adalah terdapat Sebagian kecil yang masih mengalami kesulitan belajar matematika. Kata Kunci: Kesulitan Belajar, Siswa, Pembelajaran Matematika.